2012
DOI: 10.1128/jvi.01269-12
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Induction during Influenza Virus Infection Increases Susceptibility to Secondary Streptococcus pneumoniae Infection by Negative Regulation of γδ T Cells

Abstract: The majority of deaths following influenza virus infection result from secondary bacterial superinfection, most commonly caused by Streptococcus pneumoniae. Several models have been proposed to explain how primary respiratory viral infections exacerbate secondary bacterial disease, but the mechanistic explanations have been contradictory. In this study, mice were infected with S. pneumoniae at different days after primary influenza A (X31) virus infection. Our findings show that the induction of type I interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
182
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(195 citation statements)
references
References 48 publications
7
182
0
6
Order By: Relevance
“…We detected prolonged and systemically increased levels of IL-6, which alone or together with type I IFNs induced by PR8 and S. pneumoniae (63,64) could account for the exaggerated ASC response in the medLN of PR8ϩSp-coinfected mice at day 10 p.i. This model is consistent with studies that demonstrated that IL-6, IFN-␥, and type I IFNs can enhance Ab responses (30,(65)(66)(67).…”
Section: Discussionmentioning
confidence: 81%
“…We detected prolonged and systemically increased levels of IL-6, which alone or together with type I IFNs induced by PR8 and S. pneumoniae (63,64) could account for the exaggerated ASC response in the medLN of PR8ϩSp-coinfected mice at day 10 p.i. This model is consistent with studies that demonstrated that IL-6, IFN-␥, and type I IFNs can enhance Ab responses (30,(65)(66)(67).…”
Section: Discussionmentioning
confidence: 81%
“…Likewise, Wu et al (2015) showed the CD4 + T-cell population to be reduced during post-influenza pneumococcal infection. Moreover, influenza virus infection has been demonstrated to impair the release of IL-17 by TH17 cells and IL-17-producing gd T-cells during secondary infection of mice with bacteria (Kudva et al, 2011;Li et al, 2012). This aberrant production has been attributed to deficient IL-23 production by DCs (Kudva et al, 2011) and to suppressive effects of type I IFNs released during primary viral infection (Li et al, 2012).…”
Section: Alveolar Macrophages (Ams)mentioning
confidence: 99%
“…The host adaptive immune response is largely responsible for controlling the influenza virus infection. It has been reported that coinfection could dysregulate Th17 (15) and gamma/delta T cells (16). However, whether the B cell response would be modulated during the coinfection is still not clear.…”
mentioning
confidence: 99%